(untitled) (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2016)
This document shows the technological development based on a display system and control variables, which through an electric and electronic circuit, provides the necessary information about the variables involved in the operation of pumps such as: voltage, current and pressure. The pump is located at the Basic Sciences and Technology bulding of the University of Quindio. The variables are displayed and permanently controlled during operation improving the water supply plant process. This technological development was designed with the purpose of reducing costs through increasing the useful life of the plant components and minimizing energy and water consumption. The implementation is based by a board built on Arduino mega 2560, which receive and process information from the sensors involved in the process.